Beyond technological realism: high-fidelity clinical simulation for competency-based training in medical students. A systematic review. - Batista Garcet, Yoiler; Villavicencio Cedeño, Lissette Beatriz; Macías Mendoza, Jacqueline; Azúa Menéndez, Marieta del Jesús (Spanish Journal of Medical Education, 2026)
Introduction: High-fidelity clinical simulation is used to train complex competencies before students undertake autonomous patient care, yet uncertainty remains regarding the added value of technological realism over less costly educational designs. Objective: To evaluate the effectiveness of high-fidelity clinical simulation for competency development in medical students and identify the educational conditions associated with better outcomes. Methods: A systematic review was conducted in accordance with PRISMA 2020. Studies published from January 2010 to 2 August 2026 were searched in PubMed/MEDLINE, Scopus, Web of Science, ERIC, CINAHL, SciELO and LILACS. Experimental and quasi-experimental studies involving undergraduate medical students were eligible. Narrative synthesis followed SWiM; risk of bias was assessed using RoB 2 or ROBINS-I. Results: Three hundred records were identified and 30 studies involving 4,216 students were included. High-fidelity simulation frequently improved procedural performance, clinical reasoning, recognition of deterioration and teamwork, particularly when deliberate practice, feedback and structured debriefing were present. However, direct comparisons with lower-fidelity or active educational alternatives showed inconsistent superiority. Ten studies assessed retention; transfer to real patients and clinical outcomes were rarely examined. Stress and overconfidence were potential adverse effects. Conclusions: High-fidelity simulation is most useful for integrated, dynamic competencies rather than isolated skills. Effectiveness depends primarily on alignment among objectives, difficulty, practice, debriefing and assessment. The minimum sufficient fidelity should be selected for each competency, with explicit evaluation of retention and transfer.